CPC-028 Centralized Therapy Review: Development and Validation of a Screening Tool to Detect Potential Interventions. (12th March 2013) - Declercq, P; Robeyns, AS; der Linden, L Van; Willems, L; Spriet, I
Abstract : Background: The Centralized Therapy Review study (CenTRe study), a prospective observational study carried out in the pharmacy dpt. from University Hospitals Leuven in 2011[1], showed that for almost 1 in 4 prescriptions potential interventions containing treatment corrections or pharmacotherapeutic advice could be made by the dispensing pharmacist. Based on these findings, the development and validation of a standardised screening tool to retrieve potential interventions during drug dispensing is the obligatory second step in the implementation of Centralized Therapy Review in routine daily practise. Purpose: To develop and validate the CenTRe 2 list, a standardised screening tool, used at the level of drug distribution, to review prescriptions and retrieve potential interventions in a standardised way. Materials and Methods: The CenTRe 2 list was developed by consensus by a team of ten clinical pharmacists, the CenTRe group. It is mainly based upon findings from the CenTRe study, supplemented with evidence from the literature [2–22]. Content was validated using the content validity index method [23–25] by a panel of experts (4 clinicians specialising in pharmacology, intensive care and geriatrics and 8 pharmacists who were not member of the CenTRe group). Inter-rater reliability was calculated using Cohen's kappa statistic [26]. A case format was used: all potential interventions retrieved by 12 pharmacists, which screened 20 treatment regimens using the CenTRe2 list, were compared with a gold standard. Results: The CenTRe 2 list retained 8 topics as valid (I-CVI κ*³0.75 and S-CVI/ave = 0.95) and passing the inter-rater reliability test (κaverage = 0.92 and 0.73; κmedian = 0.93 and 0.72). Conclusions: The CenTRe 2 tool is a valid and reliable tool for screening treatment regimens for potential interventions in a standardised way. A prospective observational study, using the CenTRe 2 tool, has been conducted to establish its utility in optimising patient treatment. No conflict of interest.